Microdifractional analysis of the structure of high-speed cellular crystallization of silumine; Gas Discharge Plasmas and Their Applications (GDP 2019) - Rygina M. E.; Petrikova Е. А.; Teresov А. D.; Tolkachev O. S. Oleg Sergeevich; Ivanov Yu. F. Yuriy Fedorovich (2019, 2019)
Заглавие с титульного экрана